Serum Cholinesterases, a Novel Marker of Clinical Activity in Inflammatory Bowel Disease: A Retrospective Case-Control Study - Xiaona Shao; Lei Yang; Keyue Hu; Ruiwei Shen; Qunqun Ye; Xiaogang Yuan; Qiang Zhao; Jianwei Shen (Hindawi Limited, 2020)
Background. The aim of our study was to investigate whether serum cholinesterase (ChE) levels were associated with inflammatory bowel disease (IBD). Materials and Methods. We conducted a retrospective case-control study to clarify the relationship between serum ChE levels and IBD that included 142 patients with ulcerative colitis (UC), 60 patients with Crohn's disease (CD), and 264 healthy controls (HCs). We used ROC curves to evaluate the diagnostic value of serum ChE levels for IBD. Results. Substantially lower serum ChE levels were detected in patients with UC than in HCs (6376 U/L versus 8418 U/L, P<0.001) and in patients with CD than in HCs (5181 U/L versus 8418 U/L, P<0.001). Additionally, patients with CD displayed significantly lower serum ChE levels than patients with UC (5181 U/L versus 6376 U/L, P<0.01). We also found that there was a negative association between serum ChE levels and the Crohn's Disease Activity Index (CDAI) score of patients with CD (P=0.011) and the Simple Clinical Colitis Activity Index (SCCAI) score of patients with UC (P=0.018). The area under the curve (AUC) for serum ChE for the diagnosis of IBD was 0.826, and the AUCs of serum ChE for the diagnosis of CD and UC were 0.890 and 0.800, respectively. Conclusions. Serum ChE levels have important clinical significance in the diagnosis and assessment of clinical activity in patients with IBD, and the cholinergic anti-inflammatory pathway may provide new ideas for targeted treatment of IBD.